STRUKTUR, PERILAKU DAN KINERJA PEMASARAN BIJI KAKAO DI KABUPATEN PARIGI MOUTONG PROVINSI SULAWESI TENGAH - Ihdiani Abubakar; Dedi Budiman Hakim; Ratna Winandi Asmarantaka (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2016)
Parigi Moutong is one of cocoa production center in the Central Sulawesi province. The problem faced by cocoa farmers in Parigi Moutong is the weak bargaining position of farmers in the price determination. The purpose of this study is to analyze cocoa beans market structure, conduct and performance at Parigi Moutong district. The methods used are market concentration and exit barriers to analyze market structure; market conductand farmer share and marketing margin to analyze market performance. The results show that the market of cocoa beans has four marketing channels which the highest total margin is on 2nd channel (Rp 25 465 and oligopsony structure. The most efficient marketing channel is channel 3 with 58.01 percent of farmer share. One of alternatives to increase farmer’s bargaining position in determining the cocoa price is by improving the cocoa quality through fermentation. This can be conducted by the farmer empowerment systematically and sustainably.